Immunohistochemical analysis of E-cadherin and Caspase-3 expression in equine penile squamous cell carcinoma - Nascimento, Vitória Souza de Oliveira; Pinheiro, Gilmar de Oliveira; Momo, Claudia (Brazilian Journal of Veterinary Pathology, 2024)
Neoplasms are an important cause of morbidity and mortality in horses, with squamous cell carcinoma (SCC), also called squamous cell carcinoma, being the most common genital malignant tumor in the species and the most common neoplasm in horses in the State of São Paulo. Neoplasms frequently infiltrate the corpus cavernosum and can cause metastases in regional lymph nodes, generally having a guarded to poor prognosis due to local invasion and recurrence. Given the importance of the disease, the objective was to verify whether there is a difference in the expression pattern of immunomarkers of apoptosis and cell adhesion, according to the degree of cellular differentiation of the neoplasms. Twenty equine penile SCC samples from the Animal Pathology Service of the Veterinary Hospital of the Faculty of Veterinary Medicine and Animal Science of the University of São Paulo were histologically analyzed and classified according to their degree of differentiation. In addition, they were also subjected to the immunohistochemistry technique, with the immunomarkers Caspase-3 and E-cadherin. Data were analyzed using Kendall’s correlation and the Mann-Whitney test. It was found that there is a positive correlation between the expression of immunomarkers and that there is no statistically significant difference in the expression of immunomarkers according to the degree of differentiation.